THE IMPLEMENTATION OF LARGE-SCALE ASSESSMENTS IN BRAZIL THE TRAJECTORY OF THE SAEB AND SAERS TESTS AND THEIR IMPLICATIONS AS PUBLIC POLICY IN THE SCHOOL ENVIRONMENT: THE TRAJECTORY OF THE SAEB AND SAERS TESTS AND THEIR IMPLICATIONS AS PUBLIC POLICY IN THE SCHOOL ENVIRONMENT (Interdisciplinary Studies Journal, 2025)
: Due to the growth of research in the field of public policies, specifically in education, since the 1980s, with the re-democratization and expansion of graduate studies in Brazil, the state sought ways to produce diagnostics that could reflect or measure the quality of Brazilian public education. This article presents the chronology of the process of implementing large-scale assessments, using a qualitative methodology based on bibliographic research. Its objective is to contribute to discussions on the subject by reviewing the history of the SAEB and SAERS exams and the consolidation of current application standards in schools in Rio Grande do Sul. The results showed that the production of quantifiable data through large-scale assessments has become indispensable for the development of public policies and that external assessment processes impact the actions and reactions of the various actors involved in the school environment.
Keywords: Educational Public Policies; Large-Scale Assessments; SAEB; SAERS